Tailoring eg Orbital Occupancy of Fe in Ni-Doped Na4.3Fe3(PO4)2P2O7 Cathode for High-Performance Sodium-Ion Batteries - Wang, Xiaoxue; Xu, Yuhui; Zhang, Jianhua; Xi, Yukun; Hou, Ningjing; Chen, Yixuan; Liu, Dongzhu; Yang, Zihao; Wen, Haocheng; Kang, Jia; Yang, Xiaoli; Song, Xuexia; et al. (Nano-Micro Letters, 2026)
Na4Fe3(PO4)2P2O7 (NFPP) is regarded as a prospective cathode for sodium-ion batteries (SIBs) because of its high structural stability and cost-effectiveness. However, its practical application is hindered by intrinsically low electronic conductivity. Herein, an unconventional electron transfer mechanism from Ni2+ to Fe3+ ions is unveiled in Ni-doped Na4.3Fe3(PO4)2P2O7 (NFPP-Ni) cathode, which facilitates electronic coupling within the Fe−O−Ni coordination unit and thereby effectively boosts electron transport. Moreover, the redox kinetics and reversibility of NFPP materials are predominantly governed by the degree of Fe−O covalency. The intermediate eg occupancy of Fe2+, modulated by the presence of Ni2+, optimizes the overlap between Fe d and O p orbitals. The adjustment of Ni dopant strikes a balance between accelerating Na+ diffusion kinetics and mitigating lattice strain during cycling. As a result, the NFPP-Ni electrode displays impressive rate capacity (121.0 mAh g−1 at 0.1C / 80.9 mAh g−1 at 10C) and stable cyclability (89.1% capacity retention after 1000 cycles). More importantly, the relationship between Fe eg orbital occupancy and Fe−O covalency in NFPP as modulated by various transition metal cations (Ni2+, Mn2+, Zn2+, Co2+ and Cu2+) with different electron configurations are systematically elucidated, thereby providing insights for the commercial development of sodium-ion batteries (SIBs). Highlights: 1 The Na4.3Fe3(PO4)2P2O7-M cathode constructed by various transition metal cations (M = Ni2+, Mn2+, Zn2+, Co2+ and Cu2+) with different electron configurations for sodium-ion batteries. 2 The Na4.3Fe3(PO4)2P2O7-Ni cathode exhibits superior electronic conductivity, high-rate performance and stable cyclability. 3 A quantitative relationship between the eg occupancy of Fe and the electrochemical activity of The Na4.3Fe3(PO4)2P2O7-M is proposed, serving as an activity descriptor.